Identification of SKOR2 IgG as a novel biomarker of paraneoplastic neurologic syndrome - Rezk, Mohamed; Pittock, Sean J.; Kapadia, Ronak K.; Knight, Andrew M.; Guo, Yong; Gupta, Pranjal; LaFrance-Corey, Reghann G.; Zekeridou, Anastasia; McKeon, Andrew; Dasari, Surendra; Mills, John R.; Dubey, Divyanshu (Frontiers in Immunology, 2023)
Introduction The development of new autoantigen discovery techniques, like programmable phage immunoprecipitation sequencing (PhIP-Seq), has accelerated the discovery of neural-specific autoantibodies. Herein, we report the identification of a novel biomarker for paraneoplastic neurologic syndrome (PNS), Sloan-Kettering-Virus-Family-Transcriptional-Corepressor-2 (SKOR2)-IgG, utilizing PhIP-Seq. We have also performed a thorough clinical validation using normal, healthy, and disease/cancer control samples. Methods Stored samples with unclassified staining at the junction of the Purkinje cell and the granule cell layers were analyzed by PhIP-Seq for putative autoantigen identification. The autoantigen was confirmed by recombinant antigen-expressing cell-based assay (CBA), Western blotting, and tissue immunofluorescence assay colocalization. Results PhIP-Seq data revealed SKOR2 as the candidate autoantigen. The target antigen was confirmed by a recombinant SKOR-2-expressing, and cell lysate Western blot. Furthermore, IgG from both patient samples colocalized with a commercial SKOR2–specific IgG on cryosections of the mouse brain. Both SKOR2 IgG-positive patients had central nervous system involvement, one presenting with encephalitis and seizures (Patient 1) and the other with cognitive dysfunction, spastic ataxia, dysarthria, dysphagia, and pseudobulbar affect (Patient 2). They had a refractory progressive course and were diagnosed with adenocarcinoma (Patient 1: lung, Patient 2: gallbladder). Sera from adenocarcinoma patients without PNS (n=30) tested for SKOR2-IgG were negative. Discussion SKOR2 IgG represents a novel biomarker for PNS associated with adenocarcinoma. Identification of additional SKOR2 IgG-positive cases will help categorize the associated neurological phenotype and the risk of underlying malignancy.